Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Rawat Inap di Rumah Sakit Ibu dan Anak Santa Anna - Andreas Suhendi; Fransiska Wahyu Lestari; Bernadeta Bernadeta (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2023)
Todays, hospitals must be able to provide services that are fast, accurate, qualified, and affordable, which in turn can provide satisfaction in the treatment based on desired, hospitals with the good quality are highly dependent on existing resources, such as the doctor services, nurses, staff / employees as well as available facilities and infrastructure, including environmental security, so it creates satisfaction and trust towards the hospital. RSIA Santa Anna as one of the hospitals in Bandarlampung, where the service quality is an important factor so that patients become satisfied and even loyal to RSIA Santa Anna. This study is descriptive study, the population in this study are patients at RSIA Santa Anna, determining the sample using non-probability sampling. namely random sampling techniques so that the number of samples is 100 patients and their family. The data analysis technique used is a simple linear regression model and the hypothes test used is the t test. The result shows that customer satisfaction will increase by 86% if the service quality is improved. The quality of service affects patient satisfaction by 94.0%, this is reinforced by the result of hypothesis testing which showing that the effect of service quality towards patient satisfaction is very important.